2018
DOI: 10.1007/s10534-018-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes associated with inflammation and iron metabolism in 3T3-L1 cells induced with macrophages-conditioned medium, glucose and iron

Abstract: Obesity is characterized by a chronic inflammatory process, with an increased volume of total adipose tissue, especially visceral, which secretes pro-inflammatory cytokines such as TNF-α and IL-6. Hepcidin (Hpc), a main iron metabolism regulator, is synthetized by an IL-6 stimuli, among others, in liver and adipose tissue, favoring an association between the inflammatory process and iron metabolism. Still there are questions remain regarding the interaction of these factors. Our aim was to study the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…This was confirmed by our previous study, which additionally revealed that HG did not affect the expression level of CBS (30). Several studies have also suggested that HG significantly increases the secretion of cytokines, including tumor necrosis factor-α (TNF-α), IL-6, monocyte chemoattractant protein-1 and adiponectin (31,32). However, the effect that this HG-induced reduction in CSE expression and H 2 S production has on the expression of the NLRP3 inflammasome remains unknown.…”
Section: Introductionsupporting
confidence: 83%
“…This was confirmed by our previous study, which additionally revealed that HG did not affect the expression level of CBS (30). Several studies have also suggested that HG significantly increases the secretion of cytokines, including tumor necrosis factor-α (TNF-α), IL-6, monocyte chemoattractant protein-1 and adiponectin (31,32). However, the effect that this HG-induced reduction in CSE expression and H 2 S production has on the expression of the NLRP3 inflammasome remains unknown.…”
Section: Introductionsupporting
confidence: 83%
“…In addition to the modulation by iron of adiponectin and leptin-important regulators in themselves of metabolism, appetite, and insulin signalingiron also regulates inflammatory cytokines produced by adipocytes. In cultured 3T3-L1 adipocytes, for example, iron increases interleukin 6 (IL-6) and tumor necrosis factor α (TNF-α) mRNA (86). Interestingly, iron accumulation in the absence of increased dietary exposure is seen in adipocytes in ob/ob (lep −/− ) mice, consistent with the effects of obesity on iron handling described in Section 4 (87).…”
Section: Other Inflammatory Adipokinessupporting
confidence: 56%
“…Pan et al (2014) [ 10 ] demonstrated that a high-saccharide environment inhibits the expression of one of the H 2 S-producing enzymes, cystathionine-γ-lyase (CSE), in adipocytes. Several studies have also suggested that high glucose intake significantly increases the secretion of pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), IL-6, and monocyte chemoattractant protein-1 [ 11 , 12 ], and the involved mechanism is partly related to inhibition of the CSE/H 2 S system.…”
Section: Introductionmentioning
confidence: 99%